Polyphenol-rich extract of Aronia melanocarpa inhibits TNF-? induced apoptosis in H9c2 cells - Borecki, Krzysztof; Żuchowski, Marta; Siennicka, Aldona; Adler, Grażyna; Jastrzębska, Maria (Journal of Medical Science, 2016)
Introduction. In certain pathological states within cardiovascular system, cardiomyocytes may exhibit overexpression of TNF-? that results in induction of myocardial oxidative stress and cardiac cells apoptosis. Thus, they may participate in development and progression of post-infarct congestive heart failure. The aim of this study was to evaluate the effect of polyphenol-rich Aronia melanocarpa extract (AME) on TNF-? induced apoptosis in cardiomyoblast H9c2 cells. Material and Methods. Apoptosis was measured in H9c2 cells preincubated with increasing concentrations of commercial extract of aronia – Aronox (10–50 µg/mL) for 24h and then treated with TNF-?: 100 ng/mL for 24h as well. The MTT assay was used to determine cardiomyoblasts viability. Alteration of the mitochondrial membrane potential, specific for apoptotic cells, was evaluated with caspase-3 activity assay kit. Results. Our results showed that AME significantly inhibited TNF-? induced apoptosis (IC50 = 55.84 µg/mL) and cytotoxicity in H9c2 cells. Significant inhibition of apoptosis was observed in all tested concentrations of AME. The highest anti-apoptotic and cytoprotective effect was observed at the highest concentration (50 µg/mL), while in lower the concentrations cytoprotective effect was statistically insignificant. Conclusions. Polyphenol-rich AME exhibits anti-apoptotic and cytoprotective effect in H9c2 cardiomyoblasts treated with TNF-?. Further studies are required in context of its possible application in prevention and/or therapy of cardiovascular diseases.